2015
DOI: 10.5578/mb.9024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Seasonal Distribution of Respiratory Viruses in Patients with Acute Respiratory Tract Infections, 2002-2014

Abstract: The aim of this study was to investigate the prevalence and seasonal distribution of respiratory viruses in pediatric and adult outpatients and inpatients who were admitted to hospital with the symptoms of upper and lower respiratory tract infections, during a 12-year period. A total of 5102 clinical samples (4372 nasopharyngeal swabs, 316 bronchoalveolar lavages, 219 transtracheal aspirates, 163 nasopharyngeal aspirates, 20 sputum, 10 nasal swabs) examined in our laboratory between January 1st 2002 and July 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
5
18
2
Order By: Relevance
“…Coinfection was not uncommon in this study, in which 17.3% of the infected patients had dual infection consistent with a recent study from Turkey [34]. However, it is higher than previously reported rates in children from Saudi Arabia [5,17] most likely due to the methodological differences between the studies.…”
Section: Discussionsupporting
confidence: 90%
“…Coinfection was not uncommon in this study, in which 17.3% of the infected patients had dual infection consistent with a recent study from Turkey [34]. However, it is higher than previously reported rates in children from Saudi Arabia [5,17] most likely due to the methodological differences between the studies.…”
Section: Discussionsupporting
confidence: 90%
“…Children below 5 years of age comprised of 35% of all patients enrolled in this study while the RSV detection rate in children under 5 years of age was 76%. This rate was high compared to the findings reported in USA and Turkey with 18% and 24.5% respectively (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).Similar to our findings, Weber et al reported higher percentage of RSV-infection in children less than 6 months of age in developing countries (16). In this study, the higher percentage of RSV infection among infants may probably be due to nosocomial spread of the virus within paediatric care units during the high circulating season of RSV.…”
Section: Discussioncontrasting
confidence: 50%
“…Moreover in an other study from Turkey Çiçek et. 40 Antibiotics were administered to three quarters of positive patients (270/357; 75.7%) in our population. Although viruses are the most common cause of acute respiratory tract infections, the main etiological diagnosis is often missed and unnecessary or inappropriate antibiotic use is seen in more than 50% of acute respiratory tract infections worldwide 11 .…”
Section: Discussionmentioning
confidence: 90%